Perceived Relevance and Privacy Concern Regarding Online Behavioral Advertising (OBA) and Their Role in Consumer Responses. Issue 1 (2nd January 2017) - Kim, Hyejin; Huh, Jisu
ABSTRACT: This study investigated consumer responses to online behavioral advertising (OBA), particularly focusing on the role of perceived ad relevance and privacy concern as key perceptual factors influencing consumers' attentional, attitudinal, and behavioral responses to such ads. An online survey with a sample of 292 U.S. consumers reveals that the respondents were somewhat strongly concerned about privacy risks regarding the collection and potential misuse of consumers' online activity data, but did not seem to perceive OBA to be particularly personally relevant. However, perceived ad relevance was found to be a strong positive predictor of consumer responses to OBA, while privacy concern appeared to play a negative, yet less important, role.